The burden of cancers associated with HIV in the South African Public Health Sector, 2004-2014 - Dhokotera Tafadzwa (My University, 2019)
The impact of South Africa's high human immunodeficiency virus (HIV) burden on cancer risk is not fully understood, particularly in the context of antiretroviral treatment (ART). We examined national cancer trends and excess cancer risk in people living with HIV (PLHIV) compared to those who are HIV-negative. We used probabilistic record linkage to match cancer records provided by the National Cancer Registry to HIV data provided by the National Health Laboratory Service (NHLS). We also used a text search of specific HIV terms from the clinical section of pathology reports to determine the HIV status of cancer patients. We used logistics and Joinpoint regression models to evaluate the risk and trends in cancers in PLHIV compared to HIV-negative patients from 2004-2014. In sensitivity analysis, we used inverse probability weighting (IPW) to correct for possible selection bias. A total of 329 208 cancer cases from public sector laboratories were reported to the NCR from 2004-2014 with the HIV status known for 95 279 (28.9%) cancer cases. About 50% of all female cancer cases (n=30 486) with a known status were HIV-positive. PLHIV were at higher risk of AIDS-defining cancers (Kaposi sarcoma [adjusted OR:134.01, 95% CI:111-162], non-Hodgkin lymphoma [adjusted OR:2.73, 95% CI:2.56-2.91] and, cervix [ adjusted OR:1.7, 95% CI:1.63-1.77], conjunctival cancer [adjusted OR:21.5, 95% CI:16.3-28.4] and human papillomavirus (HPV) related cancers (including; penis [adjusted OR:2.35, 95% CI: 1.85-2.99]), and vulva [ adjusted OR: 1.94, 95% CI: 1.67-2.25] compared to HIV-negative patients. Analysis using the Inverse Probability Weighting yielded comparable results. There is a need for improved awareness and screening of conjunctiva! cancer and HPV-associated cancers at HIV care centers. Further research and discussion are warranted on inclusive HPV vaccination in PLHIV.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Epidemiology: Epidemiology and Biostatistics.